2021
DOI: 10.22266/ijies2021.0430.39
|View full text |Cite
|
Sign up to set email alerts
|

Design and FPGA Implementation of Immune-PID Controller Based on BBO Algorithm for Heart Rate Regulation

Abstract: In this paper an optimal Immune-Proportional-Integral-Derivative (Immune-PID) scheme is suggested to control to the heart rate of humans and regulate it, based on Yanagihara, Noma, and Irisawa (YNI) as mathematical model of the heart rate. The parameters of the suggested immune PID controller are optimized by using Biogeography-Based-Optimization (BBO) algorithm. In addition, the proposed controller scheme is implemented using Field Programmable Gate Array (FPGA) due to its great data storage capacity, low con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…So far, the system designed in this way has high program readability, high logic synthesis efficiency, and good program portability. Without phase truncation, the output phase sequence of the phase accumulator Y½n is as follows [5,6]:…”
Section: Electromagnetic Occlusion Algorithmmentioning
confidence: 99%
“…So far, the system designed in this way has high program readability, high logic synthesis efficiency, and good program portability. Without phase truncation, the output phase sequence of the phase accumulator Y½n is as follows [5,6]:…”
Section: Electromagnetic Occlusion Algorithmmentioning
confidence: 99%
“…This model accurately models the behavior of the three main components of the heart, and it does not accurately simulate the behavior of real ECG signals. Eman F. Mohsin et al 28 had suggested an optimal immune‐proportional‐integral‐derivative (immune‐PID) strategy to manage the human's heart rate. However, a chattering problem arises, which reduces the performance of the PID controller.…”
Section: Introductionmentioning
confidence: 99%